Meta Analisis Efektivitas Model Pembelajaran Problem Based Learning dan Problem Solving Terhadap Kemampuan Berpikir Kritis pada Mata Pelajaran Matematika Kelas V - Ratana Subha Tusitadevi; Suhandi Astuti (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research uses a type of meta-analysis. The implementation was carried out from February to March 2021. There were 18 article data analyzed, nine research on Problem Based Learning (PBL) learning models and nine Problem Solving learning models. The average percentage of the PBL learning model from the low 2% was the highest 18.09% the average was 11.30%. While the percentage value of the Problem Solving learning model from the low is 2.62% and the highest is 21.06% the average is 8.43%. The results of the hypothesis using the Ancova test, namely Univariate, stated a significant value of 0.001, which means that it is smaller than 0.05 (0.001 <0.05). From the Ancova test, it states that f count> f table is 15,539> 6.74 and the significance is 0.001 <0.05, which indicates that Ho is rejected and Ha is accepted. The results of the hypothesis state that there is a significant difference in applying the Problem Based Learning and Problem Solving learning models to the critical thinking skills of class V students in mathematics.